Analytical analysis of graphene oxide ethylene glycol and graphene oxide blood base nanofluid over a vertical surface - Rehman, Ali; Guedri, Kamel; İnç, Mustafa; Alqahtani, Rubayyi T. (World Scientific Publ Co Pte Ltd, 2023)
This work considers the analytical analysis of graphene oxide ethylene glycol and graphene oxide blood base nanofluid over a vertical sheet. The principal objective of this study is to make an effort to improve the heat transfer ratio, which is the core part of the engineering and industrial sectors. Following a continuity check, the problem is modeled using the conservation rules of momentum and energy. Nonlinear PDEs are produced through modeling, which are then transformed into ODEs using the similarity transformation and thermophysical characteristics. The resultant ODEs are resolved using the Homotopy Asymptotic Method, and graphical interpretations are given to highlight the influence of different contributing parameters such as unsteady parameter, nanoparticle volume fraction, mixed convection parameter, Grashof number and Prandtl number on the velocity profile and temperature distribution. It is noted that increasing the values of nanoparticle volume fraction and stretching parameter slow down the velocity profile. Also, increasing the values of mixed convection parameter and Grashof number (Gr) enhance the velocity profile, and increasing values of Prandtl number and Graship number reduce the temperature distribution. The Nusselt number and the skin friction are examined through graphical representation. It is noted that increasing the value of mixed convection parameter decreases the skin friction of the fluids, and the Nusselt number decreases with the growing value of Prandtl number.
Keywords: Nanofluid; vertical surface; coupled equation; Homotopy Asymptotic Method